The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1113/jphysiol.2010.201194
|View full text |Cite
|
Sign up to set email alerts
|

The human circadian system adapts to prior photic history

Abstract: Non-technical summary The human biological clock organizes and regulates the timing of many biochemical and physiological processes, including the timing of sleep, on a daily basis. Light is the strongest time cue to the circadian clock that keeps these rhythms entrained to the 24 h day. Light exposure at night results in 'resetting' of the clock (phase shifting). In the current study, we examined the effects of exposing subjects to two different light levels (very dim light vs. typical room light) before expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
183
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 213 publications
(191 citation statements)
references
References 20 publications
7
183
0
1
Order By: Relevance
“…In the current analyses, we assessed phase shifts over three cycles, consistent with previous studies (21-23); however, the endogenous drift over multiple circadian cycles between assessments may influence the phase shift results compared with results calculated across only one or two circadian cycles (22,24,25). Additionally, the studies were performed against a dim light background, which reduces the masking effects of light on the circadian pacemaker but can cause moderate sensitization of the system to subsequent bright LEs (26,27). Although the mean illuminances appeared to differ between the duration conditions with up to a ~45% difference between the highest mean (9,040 lux, 1 hour condition) and lowest mean intensities (6,226 lux, 2 minute condition), it is highly unlikely that this affected the phase resetting responses.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 57%
“…In the current analyses, we assessed phase shifts over three cycles, consistent with previous studies (21-23); however, the endogenous drift over multiple circadian cycles between assessments may influence the phase shift results compared with results calculated across only one or two circadian cycles (22,24,25). Additionally, the studies were performed against a dim light background, which reduces the masking effects of light on the circadian pacemaker but can cause moderate sensitization of the system to subsequent bright LEs (26,27). Although the mean illuminances appeared to differ between the duration conditions with up to a ~45% difference between the highest mean (9,040 lux, 1 hour condition) and lowest mean intensities (6,226 lux, 2 minute condition), it is highly unlikely that this affected the phase resetting responses.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 57%
“…In experiments with human subjects, the circadian system was found to be adaptive and maintain a high plasticity, as prior exposure to dim light was shown to influence MLT suppression following more intensive light stimuli (Jasser et al, 2006;Chang et al, 2011). According to our results, long AD causes the decrease in response in regard to hsp70 expression and protein levels, probably because the animal becomes used to the LI.…”
Section: Discussionmentioning
confidence: 69%
“…For instance, an increased sensitivity to light may develop with age to compensate for chronic exposure to lower levels of light due to lens opacification. Several studies in young individuals have shown that, following prolonged exposure to low light levels, exposure to light induces stronger suppression and phase shift of melatonin secretion (Chang et al, 2011;Hebert et al, 2002;Jasser et al, 2006). An alternative explanation for the smaller pupil size in the elderly, despite the lack of a difference in relative pupil constriction, is a loss of tonic control of pupil dilation, previously suggested in a study of nonhuman primates (Clarke et al, 2003).…”
Section: Discussionmentioning
confidence: 99%